Program Pengajian Dalam Meningkatkan Pemahaman Nilai-Nilai Pendidikan Aqidah Dan Ibadah Pada Jama’ah Majelis Ta’lim Nurul Taqwa - Meiyanda, Rana; Mahardika, Mutiara; Asbabul Jannah, Wahyu; Sutarto; Purnama Sari, Dewi (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
Islamic study groups (pengajian) as non-formal educational institutions play a vital role in strengthening the religious understanding of Muslim communities, particularly in matters of creed (aqidah) and worship (ibadah). This study examines the implementation of the Majelis Ta’lim Nurul Taqwa in Tanjung Beringin Village, Curup Utara, Rejang Lebong Regency, and its contribution to enhancing the congregation’s grasp of core Islamic values. Using a qualitative phenomenological approach, informants were selected through a snowball sampling technique, involving the teaching ustadz, community figures, and congregation members. Data were obtained through observation, in-depth interviews, and documentation, and analyzed through data reduction, display, and conclusion drawing. The findings show that the pengajian significantly improves participants’ understanding of aqidah, particularly in reinforcing monotheism, clarifying the pillars of faith, and reducing tendencies toward syncretic practices. In the realm of ibadah, participants demonstrate better discipline in performing obligatory prayers, improved accuracy in worship practices, and stronger spiritual motivation reflected in daily behavior. These results confirm the role of majelis ta’lim as an effective medium for community-based religious education. The study contributes to the literature on non-formal Islamic education by providing empirical evidence of value internalization through routine Islamic study groups activities.